How does ethnoscience-students’ worksheet (ESW) influence in science learning? - Nisa', Khoirun; Suprapto, Nadi; Shofiyah, Noly; Cheng, Tsung-Hui (Intelektual Pustaka Media Utama, 2024)
Incorporating ethnoscience into lessons through the ethnoscience-students’ worksheet (ESW) is one method to improve student interest in science learning while introducing them to the local culture. However, no research was reported the effects of ESW on students' responses and the factors that influence ESW implementation in science learning. In order to better understand how students learn through ESW, this study investigated the relationship between ethnoscience context, science learning, and the implementation of students’ worksheets. Seventy-two students participated in the survey after they studied ethnoscience learning through ESW. Students’ responses are more influenced by science learning. In addition, the ethnoscience-integrated students’ worksheets (SW) variable indirectly affects students’ responses. Additionally, ESW affects students' responses more significantly than science learning and ethnoscience. This research provides insightful implications for educators on planning, designing, and practicing ESW to enhance students’ problem-solving motivation and academic achievement. Furthermore, to contribute significantly to future researchers, further research employed the structural equation model through covariance analysis, also known as confirmatory factor analysis (CFA).